Development of Parenteral Formulation of Poorly Water Soluble Drugs: The Role of Novel Mixed-solvency Concept (Asian Journal of Pharmaceutics (AJP), 2017)
Context: Water solubility is an important molecular property for successful drug development as it is a key factor governing drug access to biological membranes. The solubilization of poorly water soluble drug by facilitated mixed solvency is presented. Aim: The aim was to develop the injection formulations of the model poorly water-soluble drug. Settings and Design: Trial and error based experimental study. Materials and Methods: Mixed solvency approach was used to solubilize the hydrophobic drug. Mixed solvent system prepared using water-soluble hydrotropes (such as sodium citrate and urea) and water-miscible cosolvents, such as polyethylene glycol (PEG) 200, PEG 300, PEG 400, PEG 600, glycerin, propylene glycol, and ethanol. Drug was characterized using ultraviolet, Fourier Transform infrared (FT-IR), and Raman spectroscopy. Solubilizing power (Î¦) and the Gibbs free energy of transfer (Î”G0tr) were determined. Various properties of solution such as pH, viscosity, specific gravity, and refractive index were also studied. Results: Desired solubility of drug achieved in a mixed solvent blend AF5, which was more than 200 fold as compared to the solubility in distilled water 0.152 mg/ml. Drug content was found to be more than 98%. FT-IR and Raman spectroscopy results may support intermolecular hydrogen bonding between drug and mixed solvent system. Developed formulation was physically and chemically stable. Conclusion: This technique proved a synergistic enhancement in solubility of a poorly water soluble drug due to mixed solvent effect and produces a stable formulation. Mixed solvency concept may reduce the individual concentration of solubilizers and so reduce their toxicity associated with them.